Transmission of border disease virus from a persistently infected calf to seronegative heifers in early pregnancy - Braun, Ueli (BMC Vet Res, 2015)
BACKGROUND: This study describes the transmission of border disease virus (BDV) from a persistently infected calf to seronegative heifers in early pregnancy, resulting in persistently infected fetuses. On day 50 of pregnancy (= day 0 of the infection phase), six heifers were co-housed in a free stall with a bull calf persistently infected with BDV (pi BVD) for 60 days. The heifers underwent daily clinical examination, and blood samples were collected regularly for detection of pestiviral RNA and anti-pestivirus antibodies. After day 60 (= day 110 of pregnancy), the heifers were slaughtered, and the fetuses and placentae underwent post-mortem and immunohistochemical examination and RT-PCR for viral RNA detection. RESULTS: Three heifers had mild viraemia from day 8 to day 14, and by day 40 all heifers had pestivirus antibodies identified as anti-BDV antibodies in the serum neutralisation test. The placenta of the three viraemic heifers had histological evidence of inflammation, and fetal organs from these heifers were positive for pestivirus antigen by immunohistochemical examination and for BD viral RNA by RT-PCR and sequencing. Thus, co-housing of heifers in early pregnancy with a pi-BDV calf led to seroconversion in all heifers and persistent fetal infection in three. CONCLUSIONS: Considering that pi-BDV cattle can infect other cattle and lead to persistent infection of the fetus in pregnant cows, BDV should not be ignored in the context of the mandatory BVDV eradication and monitoring program. This strongly suggests that BDV should be taken into account in BVD eradication and control programs.